2015
DOI: 10.1093/eurheartj/ehv118
|View full text |Cite
|
Sign up to set email alerts
|

Atrial flutter: more than just one of a kind

Abstract: Since its first description about one century ago, our understanding of atrial flutter (AFL) circuits has considerably evolved. One AFL circuit can have variable electrocardiographic (ECG) manifestations depending on the presence of pre-existing atrial lesions, or impaired atrial substrate. Conversely, different (right sided or even left sided) atrial circuits including different mechanisms (macroreentrant, microreentrant, or focal) can present with a very similar surface ECG manifestation. The development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 58 publications
2
68
0
3
Order By: Relevance
“…Postępowanie w przypadku epizodów szybkiego rytmu przedsionkowego (AHRE) wykrytych za pomocą wszczepionego urządzenia. Zaadaptowano z raportu z trzeciej konferencji ekspertów German Competence Network on Atrial Fibrillation/European Heart Rhythm Association (AFNET/EHRA) [150]; AF -migotanie przedsionków; CHA 2 DS 2 -VASc -skala obejmująca zastoinową niewydolność serca, nadciśnienie tętnicze, wiek ≥ 75 lat (2 pkt), cukrzycę, udar mózgu (2 pkt), chorobę naczyń, wiek 65-74 lat, płeć (żeńską); EKG -elektrokardiogram rytmu komór [158]. Częstość występowania trzepotania przedsionków wynosi mniej niż 1/10 częstości występowania AF [159].…”
Section: Elektrokardiograficzne Wykrywanieunclassified
See 1 more Smart Citation
“…Postępowanie w przypadku epizodów szybkiego rytmu przedsionkowego (AHRE) wykrytych za pomocą wszczepionego urządzenia. Zaadaptowano z raportu z trzeciej konferencji ekspertów German Competence Network on Atrial Fibrillation/European Heart Rhythm Association (AFNET/EHRA) [150]; AF -migotanie przedsionków; CHA 2 DS 2 -VASc -skala obejmująca zastoinową niewydolność serca, nadciśnienie tętnicze, wiek ≥ 75 lat (2 pkt), cukrzycę, udar mózgu (2 pkt), chorobę naczyń, wiek 65-74 lat, płeć (żeńską); EKG -elektrokardiogram rytmu komór [158]. Częstość występowania trzepotania przedsionków wynosi mniej niż 1/10 częstości występowania AF [159].…”
Section: Elektrokardiograficzne Wykrywanieunclassified
“…Leczenie trzepotania przedsionków omówiono w rozdziale 13.7. Częstoskurcz spowodowany makroobwodem re-entry w obrębie lewego lub prawego przedsionka stwierdza się głównie u pacjentów po ablacji z powodu AF, chirurgicznym leczeniu AF lub innej operacji na otwartym sercu [158].…”
Section: Elektrokardiograficzne Wykrywanieunclassified
“…Left or right atrial macro re-entrant tachycardia is mainly found in patients after catheter ablation for AF, AF surgery, or after open heart surgery. 158 6. Classification of atrial fibrillation 6.1 …”
Section: Electrocardiogram Detection Of Atrial Fluttermentioning
confidence: 99%
“…Atrial flutter (AFL) is one of the most common supraventricular arrhythmias with macro-reentrant mechanism of atrial activation around an anatomical barrier with regular atrial rate ≥ 240 beats/min (1,2). Despite of recent advances in invasive electrophysiology, electrocardiography (ECG) remains one of the most effective methods used for rhythm disorders diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes we need only atrial mapping for precise diagnosis. Atrial flutter can be described as counterclockwise or clockwise typical (cavotricuspid isthmus (CTI)-dependent) and atypical by ECG (2). For clinicians, a key point of ECG diagnostics of typical AFL is to identify a "saw tooth" flutter curve with characteristic F waves in II, III, aVF and V1 leads, which are caused by AFL waves circulating in the right atrium.…”
Section: Introductionmentioning
confidence: 99%